Overprescription of opioid analgesia is common following ambulatory Otolaryngology—Head and Neck surgery procedures: A multicenter study. Issue 2 (9th March 2022) - Hamour, Amr F.; Laliberte, Frederick; Levy, Jordan; Xu, Jason; Park, Edward; Lin, Vincent; de Almeida, John; Strychowsky, Julie; Eskander, Antoine; Monteiro, Eric
Abstract: Background: The rise in the use of prescription opioids for postoperative analgesia within surgery has mirrored an increased trend of opioid‐related morbidity within Canada and the United States. This study prospectively studied daily pain levels and medication requirements postoperatively in patients undergoing elective Otolaryngology—Head and Neck surgery procedures. Methods: Patients were asked to prospectively document their pain level and medication use daily for 7 days postoperatively. A final survey was used to quantify unused medication left at home and clarify each patient's disposal plan. We included patients undergoing elective outpatient or short stay surgeries from three tertiary care centers in Toronto, Ontario from September 2016 to September 2017. Previous opioids users or patients suffering from chronic pain were excluded. Results: A final cohort of 56 eligible adult patients were included in the study. The most common procedures were thyroidectomy ( n = 19), endoscopic sinus surgery ( n = 10), tympanoplasty/ossiculoplasty ( n = 7), and cochlear implant ( n = 5). Most patients received a prescription for acetaminophen/codeine ( n = 29, 51.8%) or acetaminophen/oxycodone ( n = 22, 39.3%) and used on average 29% of their initial prescription. Patients most commonly opted to keep their unused narcotics at home ( n = 23, 41%). A total of 710 tablets of narcotics were overprescribed in our study population, 351 of which were kept in patients' home for future use. Conclusion: There is a clear tendency to overestimate postoperative pain resulting in significant overprescription of opioids among Otolaryngologists. Highlights: Surgeons tend to overestimate post‐operative opioid analgesic requirements, leading to over‐prescription. Less than half of the 56 participants in this study used non‐opioid analgesia during their post‐operative course, indicating a lack of counselling. Most commonly, patients elected to keep unused opioids at home for future use – a known risk factor for opioid diversion.